2018
DOI: 10.1002/pat.4321
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviors and characteristics of polylactide/poly(butylene succinate) blend films via reactive compatibilization and plasticization

Abstract: Polylactide (PLA)/poly(butylene succinate) (PBS) blend films modified with a compatibilizer and a plasticizer were hot‐melted through a twin screw extruder and prepared by hydraulic press. Toluene diisocyanate (TDI) and polylactide‐grafted‐maleic anhydride (PLA‐g‐MA) were used as compatibilizers, while triethyl citrate and tricresyl phosphate acted as plasticizers. The effects of the type and content of compatibilizer and plasticizer on the mechanical characteristics, thermal properties, crystallization behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Considering the fact that the use of petroleum-based plastics to toughen PLA would partially sacrice the sustainability, the exible petroleum-based synthesis polymers or biobased polymers, such as PBAT, PBS, PCL, PHAs et al [214][215][216][217] have recently been employed to toughen PLA. The wide application of biodegradable materials provides a good approach to reduce plastic pollution caused by non-biodegradable materials.…”
Section: Biodegradable Polymer-materialtoughened and Modified Plamentioning
confidence: 99%
“…Considering the fact that the use of petroleum-based plastics to toughen PLA would partially sacrice the sustainability, the exible petroleum-based synthesis polymers or biobased polymers, such as PBAT, PBS, PCL, PHAs et al [214][215][216][217] have recently been employed to toughen PLA. The wide application of biodegradable materials provides a good approach to reduce plastic pollution caused by non-biodegradable materials.…”
Section: Biodegradable Polymer-materialtoughened and Modified Plamentioning
confidence: 99%
“…Melt blending or compounding PLLA with different types of flexible polymers was one of the economic approaches to toughen PLLA . However, poly(ε‐caprolactone) (PCL) was a biodegradable aliphatic polyester with high flexibility and good biocompatibility and thermal stability, which had gained great attention as modifiers for PLLA, and the modifying results exhibited some improvements in the toughness of PLLA .…”
Section: Introductionmentioning
confidence: 99%
“…The Scanning electron microscope (SEM) micrographs of cryo-fractured surfaces of the blends. A, PLLA/PCL/19k-CL 67 LA 33 (80/20/5), B, 19k-CL 51 LA 49 (80/20/5), C, 19k-CL36 LA 64 (80/20/5), and D, 19k-CL19 LA 81 (80/20/5) rheological properties of PLLA/PCL/PCL-b-PLLA (80/20/10) ternary blends were displayed in Figures 5 and 6, respectively. The plots of the complex viscosity (η*) vs ω and Cole-Cole (η″ vs. η′) were applied to analyze the compatibility of melting blends.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the termination reactions, chain scission by either back‐biting or thermo‐hydrolysis may also occur. [ 33 ] Mani et al [ 28 ] also reported the occurrence of β‐scission of the polyester macroradical during the melt grafting reaction of maleated PBS, leading to the formation of radical chains and vinylidene chain ends, especially in the presence of an organic peroxide initiator. Since the grafting reaction was conducted at 160°C; which is above the ceiling temperature of MA (≥150°C), the poly(MA n ) was not present in the compatibilizer.…”
Section: Resultsmentioning
confidence: 99%